Interface web development for analysis of item response theory with mixed model approach and application on bank soal MGMP - T C P Utama; I Made Tirta; M Fatekurrahman (Pascasarjana Universitas Pendidikan Indonesia, 2018)
The development of the world of education today is progressing very rapidly, the era of technology is increasingly modern, so that teachers must have adequate competence in every process of teaching and learning activities. One type of measurement often done in education are measurement of the students’ performance both for cognitive and effective aspects. These measures are extremely important therefore must use a good measuring tool and the results also easy to interpret. The measurement of students performance mostly use tests. Items response theory have evolved from traditional one to modern theories to apply more realistic models which are known as item response theory. However the use of modern test theory much rely on availability of the computer software. In this paper we report the development of a web-GUI interface that can be used to analyze polytomous responses, using Hierarchical Generalized Linear Models which will also contains theories and interpretations of the results. This web-GUI interface is expected to help teachers to understand and to do the analysis of polytomous responses more easily.